Assessment of seasonal variations in dry eye syndrome prevalence among office workers - Prameela R; Vijaya Sree S; Ramya Bhukya (Asian Journal of Medical Sciences, 2024)
Background: Dry eye syndrome (DES) is prevalent among office workers and influenced by various environmental and individual factors. This study assesses the prevalence, seasonal variations, symptom severity, and environmental influences on DES among office workers. Aims and Objectives: The study aimed to assess the prevalence of DES among office workers in Warangal, Telangana, India, and to evaluate the impact of seasonal variations, symptom severity, and environmental factors on DES. Materials and Methods: A cross-sectional study was conducted with 100 office workers aged 25–55 years old. Data were collected through questionnaires on DES symptoms, environmental conditions, and demographics. The prevalence of DES was calculated, and seasonal variations were analyzed. Symptom severity was recorded on a scale from 1 to 10. Environmental factors such as humidity, air-conditioning use, screen time, and indoor air quality were examined for their correlation with DES prevalence. Results: The overall prevalence of DES was 45%, with females showing a higher prevalence (50%) compared to males (37.5%). Seasonal variations showed the highest DES prevalence in winter (40%) and the lowest in summer (16%). Symptom severity scores were highest in winter (6.5 overall) and lowest in summer (3.8 overall). Low humidity in winter was associated with a 55% prevalence of DES, especially among females (65%). High air-conditioning use in summer correlated with a lower DES prevalence (12.5%). Increased screen time (>6 h/day) resulted in a 60% prevalence of DES, with seasonal peaks in winter (65%). Poor indoor air quality was reported by 70% of participants and linked to a 50% prevalence of DES. Conclusion: The study highlights significant gender differences, seasonal variations, and environmental factors impacting DES prevalence and severity among office workers. Interventions focusing on improving workplace conditions, managing screen time, and enhancing indoor air quality may mitigate DES symptoms.